Effectiveness Of Data Processing and Technical Approaches in Facial Recognition Systems - Yuldasheva G. T.; Suyunov E. (Euro Asian Journal Publishing, 2024)
The article explores the methods for improving the efficiency of facial recognition systems through advanced data processing techniques and discusses the technical requirements these systems must meet.
Keywords: Artificial Intelligence; Deep Learning; Edge Computing